Pengaruh Kompensasi, Keselamatan dan Kesehatan Kerja (K3) Serta Motivasi Kerja terhadap Kepuasan Kerja Karyawan CV. Rizky Berdikari Mandiri - Vinka Anggorowati; Syaiful Anwar (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the influence of compensation, occupational safety and health, and work motivation on employee job statisfaction. Data were collected using a questionnaire distributed to employees of CV. Rizky Berdikari Mandiri. The sampling technique used was saturated sampling, with a total of 53 respondents. The analytical tool used is descriptive (primary data) by using a questionnaire which is assisted by a likert scale and given to respondents. The analytical tool used is SPSS software version 29. The results of the study show that partially Compensation and Occupational Safety and Health (K3) have a positive and significant effect on employee job statisfaction, while Work Motivation does not have a significant effect on employee job statisfaction at the CV. Rizky Berdikari Mandiri. However, the study also found that work motivation does not have a significant effect on employee job satisfaction at CV. Rizky Berdikari Mandiri. This finding suggests that while motivation is often seen as a driving factor for employee performance, other factors, such as compensation and workplace safety, may have a more direct and immediate influence on job satisfaction in this particular context. It is possible that the intrinsic and extrinsic motivators currently in place at the company may not be as effective or prominent in comparison to compensation and safety initiatives. The study concludes that while compensation and occupational safety are significant drivers of job satisfaction, work motivation should still be addressed but perhaps with more targeted strategies to ensure that employees are adequately motivated and engaged. Further research could explore how different types of motivation—intrinsic and extrinsic—affect employee satisfaction in various organizational settings.